Analisis Tingkat Kesehatan Koperasi Dilihat Dari Aspek Rentabilitas Pada Koperasi Kredit Solidaritas Santa Maria Assumpta Kota Kupang - Dangga, Lende; Liem, Jhon; Naisanu, Joritha (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
Cooperatives are the prima donna of the people of East Nusa Tenggara, because of the high level of community participation as members of cooperatives. And on the other hand, cooperatives act as a pillar for the community, especially Kupang City, for the development of cooperatives and there is high public interest in becoming members of the Santa Maria Assumpta Solidarity Credit Cooperative, Kupang City. This research was conducted at the Santa Maria Assumpta Solidarity Credit Cooperative, Kupang City from February 2020 to October 2022. The data collection method used was quantitative descriptive, namely using the Profitability ratio, with the financial report data collection technique of the Santa Maria Assumpta Solidarity Credit Cooperative Kupang City from 2020 to 2022. The results of the research show that the health analysis of the Santa Maria Assumpta Solidarity Credit Cooperative in Kupang City, in 2010 was 90.38%, in 2021 it was 92.18% and in 2022 it was 92.15% . This shows that the ratio achieved by the Solidarity Credit Cooperative from the profitability aspect has decreased.